Desarrollo de un Método de Análisis de Metabolitos de Nitrofuranos en Tejido Animal Empleando el Sistema GC/PTV/EI/MSMS - Soto Alvarado, Sonia del Carmen; Rodríguez Valdés, Osvaldo Nicolás; Rodríguez, Guillermo; Vélez López, Ernesto; Temores Peña, Juan; Velázquez Chong, Laura Renné (Acta Universitaria, 2008)
Currently, liquid phase systems are used in the analysis of metabolites of 5-nitrofuranes, connected to mass/mass LC/MSMS analyzers of which are very expensive. In this studyan alternative method is presented in which a gaseous phase system is used, with an iontrap sequential mass analyzer and a temperature programmable GC/PTV/EI/MS5 injection system, to introduce 5-nitrofuranes metabolites, at low temperature and as derivatized to avoid the thermal degradation of these compounds in the injection system. Thermally stable structures are obtained with by derivitizing the metabolites with heptafluorobutyricanhydride (HFBA) in the temperature programmable injection system, and greater structural information is also obtained. Using this method the characterization of four heptafluorobutyrates derivatives of metabolites of 5-nitrofuranes was obtained: semicarbazide(SEM), 3-amino-2-oxazolidinone (AOZ), 3-amino-5-morfolinomethyl-oxazolidinone (AMOZ)and 1-aminohydantoine (AHD) in porcine tissue at a concentration of 1Î¼g/kg.
Keywords: Array; Array; Array; Array; Array